Chile : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that Chile's economic fundamentals remain sound and have improved through the evolution of the policy regime in recent years. Yet the country is operating in a difficult environment for several years, now coping with a sequence of negative shocks. Real GDP grew by 2.8 percent in 2001, as weakening domestic demand was offset by a strong expansion of net export volumes. With a substantial decline in Chile's terms of trade, however, the external current account deficit has widened moderately, to about 2 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet